Effects of COVID-19 Pandemic and Movement Control Order Announcements on Stock Behaviors of Health Care Sectors in Malaysia - Khairunnisa Ibrahim; Colin Wong Koh King; John Francis Belen; Diana Hii Ing Ling; Abu Hassan Md Isa (New Advances in Business, Management and Economics Vol. 2, 2025)
Human capital development and health improvement are crucial goals for a sustainable and growing economy in every nation. COVID-19 was designated as a global pandemic, which had an impact on the stock market in addition to affecting human lives. This study’s main goal is to determine how the COVID-19 pandemic has affected stock returns for healthcare companies in Malaysia. This study was conducted using a quantitative approach. In this study, secondary data collection is the main source. The sample datum selected in this study is listed healthcare industry companies in Bursa Malaysia. This study is categorized into two timelines: the first concerns the impact of the COVID-19 MCO announcement, while the second focuses on the impacts of the first and second waves of COVID-19 infection announcements. The data of daily stock prices and daily market indices cover the period of six- months prior to the announcement and within a year, 2020, and the sampling frame of the research is taken the from Yahoo Finance Database Healthcare sectors are expected to have different impacts by the event according to different providers. Firms belonging to healthcare equipment and services are affected more compared to other healthcare providers. Although many countries have adopted similar measures to control the spread of the epidemic, these countries also have paid for the painful economic stagnation or retrogression. Once the first wave came, the panic spread quickly to the whole market investors behaved irrationally and the price fell drastically. However, the first wave effect gradually returned to normal in the following wave. The sample companies have more experience in responding to the waves and stabilizing the prices and investors reacted differently regarding the news of the second wave. By examining stock behaviors, investors can find possible investments in the healthcare industry and base their choices on the company’s resilience to external shocks. Policymakers and business executives may use this data to help them create plans that will increase resilience and guarantee a better outcome in similar circumstances.